EFEK METODE PEMBELAJARAN PADA HASIL BELAJAR MATEMATIKA SISWA SMP NEGERI 267 JAKARTA - Achmad Syahlani; Desy Setyorini (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
The aims of this research is to find the differences between mathematics learning achievement, and the students who are taught with free-inquiry, guided-inquiry and conventional learning method. This research carried out in SMP Negeri 267 Jakarta, whose all of grade IX students as the population and class IX-A, IX-B and IX-D as the sample, which obtained by using Cluster Random Sampling. This research uses experimental method with Static-Group Comparison design, where mathematics learning achievement as the dependent variable, learning method as the treatment (independent variable). The mathematics learning achievement data were obtained through mathematics achievement test instrument, the data were analyzed with descriptive and inferential analysis (hypothesis test) with one-way analysis of variance (ANOVA) to test that the differences exist among the means and Dunnett test for the one-way ANOVA post hoc test. This research revealed that: (1) There are differences in mathematics learning achievement, between the students who are taught with the free-inquiry, guided-inquiry and conventional learning method; (2) Mathematics learning achievement of the students who are taught with free-inquiry is higher than the conventional learning method; (3) Mathematics learning achievement of the students who are taught with guided-inquiry is higher than the conventional learning method; and (4) Mathematics learning achievement of the students who are taught with free-inquiry is not higher than the guided-inquiry learning method.